Locating Logic Faculty in the Mental System - Mohamed Eusuff, Md Amin (2022)
Taken from Chomsky’s Knowledge of Language (1986), it is noted that logical form (LF) is not a direct reflection of deep structure (D-structure). It has induced a question, where is then 'logic' located in the human psychology (in the sense of the mind-system) if it is not in the D-structure. To answer this question, we will try to see how different languages (in this paper, English, Malay and Turkish) are structured differently on the surface (S structure) yet can have the same internal syntax (D-structure). However, when there is a change in semantics (in the sense of intended meaning), a change in LF is noted, although the D-structure might remain the same. Making sense of this, we argue that D-structure is not the innermost faculty of the human innate system (mind) but rather, how S-structure is to D-structure, that is how D-structure is to the human logic faculty. In other words, with D-structure, logic faculty is more profound.